The Efficacy of New Liquid Laser Dye Material – Chalcone: 1-(4-methylsulfonyl phenyl)-3-(4-N,N-dimethyl (amino phenyl)-2-propen-1-one (MSPPP) - Attia, Mohana Faroug; Elbadawi, Abdelrahman A. (Orbital: The Electronic Journal of Chemistry, 2022)
This paper includes the efficacy of synthesis and characterization of a new liquid laser dye material – chalcone of 1-(4-methylsulfonyl phenyl)-3-(4-N,N-dimethyl (amino phenyl)-2-propen-1-one (MSPPP) and its application as a new laser medium. The absorption and fluorescence spectra of MSPPP were investigated under different solvents and concentrations. The study investigated the pump pulse energies of Nd: YAG laser (355 nm) and the amplified spontaneous emission (ASE) performance of MSPPP under various concentrations, and organic solvents. At identical conditions, the amplified spontaneous emission spectra of MSPPP in solution were compared with a conventional laser dye of coumarin 503. The fluorescence quantum yield and the gain of MSPPP were determined. The features are: (I) MSPPP has stellar photochemical stabilization., (II) ASE from the MSPPP was setting in the wavelength range between 515 and 548 nm. The molecular geometry was optimized and their HOMO– LUMO energy values were determined by SCM Software for Chemistry & Materials using DFTB (GGA BLYP) [Density-Functional based Tight-Binding] method.